PENGARUH KEPEMIMPINAN DAN KESELAMATAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN - MOH. NASIKH; ASEP KURNIAWAN (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
The purpose of this study are to find out that leadership factor and safety and healthy occupational (K3) have a significant partially effect on employee performance at PT Pertamina Patra Niaga VHS Dipo Lok Malang, and also to find out which variables between leadership and safety and healthy occupational (K3) has more partially dominant influence on employee performance at PT Pertamina Patra Niaga VHS Dipo Lok Malang. The method of analysis data used in this study are validity test method, reliability test, and multiple linear regression analysis method (F test and t test). Based on the method applied can be seen that, leadership factors have a significant partially effect on employee performance than safety and healthy occupational (K3). In addition, leadership and safety and healthy occupational (K3) factors together have a significant simultaneous effect on employee performance. It can be concluded that, leadership factors influence more dominantly on employee performance because it has a significant and partial effect simultaneously than safety and healthy occupational (K3) factors which only have a significant simultaneous effect on employee performance. The validity test of the leadership factor has greater percentage of the questionnaire statement than the safety and healthy occupational factors (K3) on employee performance with ratio of 62.5% – 30%. As for the results t test (partial) is known that, the leadership factor on employee performance has a significant value of 0,000 < 0,05 and t count (4,565) > t table (2,093), and safety and healthy occupational factors (K3) on employee performance has a significant value of 0,124 > 0.05 and t count (-1,608) < t table (2,093). While the F test (homogeneity) is known that, leadership and safety and healthy occupational (K3) factors on employee performance have a significant value of 0.001 < 0.05 and F count (11.258) > F table (3.49).